Fertilizers and Mixed Crop Cultivation of Chromium Tolerant and Sensitive Plants under Chromium Toxicity - B. Dheeba; P. Sampathkumar; K. Kannan (Journal of Toxicology)
Zea mays (maize) and Vigna radiata (green gram) are found to be the chromium (Cr) tolerant and sensitive plants, respectively. In the present paper, we investigate the reduction of the toxicity of Cr in the sensitive plants by the mixed crop cultivation in the field using various amendments. Further, the potassium dichromate was used as the source of hexavalent Cr. The results indicated that Cr adversely affects both the growth and yield of plants. The soil properties vary with Cr and different fertilizer amendments and the yield of both plants were affected by Cr. We conclude that metal accumulation of seeds of green gram was higher than corn and the application of single fertilizer either farm yard manure (FYM) or nitrogen, phosphorous, and potassium (NPK) enhances the growth and yield of both the tolerant and sensitive plants in the mixed crop cultivations.